Haemodynamic parameters associated with renal function prior to and following heart transplantation. (14th September 2021) - Baudry, Guillaume; Sebbag, Laurent; Bourdin, Juliette; Hugon‐Vallet, Elisabeth; Jobbe Duval, Antoine; Mewton, Nathan; Pozzi, Matteo; Rossignol, Patrick; Girerd, Nicolas
Abstract: Aims: Abnormal renal function is a common feature in patients on heart transplant waiting lists. This study aimed to identify the haemodynamic parameters associated with decreased estimated glomerular filtration rate (eGFR) in patients listed for heart transplantation (HT) and renal function improvement following HT. Methods and results: A total of 176 adults (52 years old, 81% men) with available right heart catheterization (RHC) listed in our centre for HT between 2014 and 2019 were studied. Cardiac catheterization measurements were obtained at time of HT listing evaluation. Changes in renal function were assessed between RHC and 6 months after HT. Median eGFR was 63 mL/min/1.73 m 2 at time of RHC. Central venous pressure > 10 mmHg was associated with a two‐fold increase in the likelihood of eGFR < 60 mL/min/1.73 m 2 at time of RHC (adjusted odd ratio, 2.2; 95% confidence interval, 1.1–4.7; P = 0.04). In the 134 patients (76%) who underwent HT during follow‐up, eGFR decreased by 7.9 ± 29.7 mL/min/1.73 m 2 from RHC to 6 months after HT. In these patients, low cardiac index (<2.1 L/min/m 2 ) at initial RHC was associated with a (adjusted) 6 month post‐HT eGFR improvement of 12.2 mL/min/1.73 m 2 ( P = 0.018). Patients with eGFR < 60 mL/min/1.73 m 2 and low cardiac index at time of RHC exhibited the greatest eGFR improvement (delta eGFR = 18.3 mL/min/1.73 m 2 ) while patients with eGFR ≥ 60 mL/min/1.73 m 2 and normal cardiac index had a marked decrease in eGFR (delta eGFR = −27.7 mL/min/1.73 m 2, P < 0.001). Conclusions: Central venous pressure is the main haemodynamic parameter associated with eGFR < 60 mL/min/1.73 m 2 in patients listed for HT. Low cardiac index prior to HT is associated with post‐transplant renal function recovery.